Upaya Kepala Madrasah Dalam Membina Budaya Religius - Muhammad Nur Hakim (Program Studi Manajemen Pendidikan, 2018)
Abstract Madrasah is an institution having Islamic. Therefore, the school is requested to maintain Islamic values ​​that can be realized in the activities of formal and non-formal learning. To facilitate the performance, Principals need Madrasah institutions that have innovations and new ideas to improve a Madrasah. On the basis of the above background, this research focuses on the how Principals efforts in fostering Islamic Culture in MA Surban Pacet Mojokerto. And, what is the problem and the impact of Principals in fostering Islamic Culture in MA Surban Pacet Mojokerto. This study aims to describe the efforts Principals in Fostering Islamic culture, as well as the problem and the impact of the development of Islamic culture. The approach of this study used a qualitative approach with a qualitative descriptive research, and collected by using observation, interviews (interviews) and documentation. Source of data: Principals of MA Surban Pacet Mojokerto, Vice Principal of Curricullum , Vice Principal of Studentship, teachers and students. The data were then analyzed using qualitative descriptive analysis techniques. Keywords: Principals, Islamic Culture